Experimental study on soot formation, evolution and characteristics of diffusion ethylene/air flames in ψ-shaped mesoscale combustors. (1st April 2019) - Chen, Mingfei; Liu, Dong; Ying, Yaoyao; Lei, Kai; Luo, Minye; Liu, Guannan; Zhang, Rui; Jiang, Bo
Graphical abstract: Highlights: Flame structure gradually becomes irregular in large inlet velocity. More soot production is obtained with the enlargement of combustor size. Different effects on soot characteristics between combustors are found. Notable distinctions in nanostructure of soot due to the scale effect are observed. Different combustion efficiencies between combustors are detected. Abstract: Soot formation, evolution and characteristics of diffusion ethylene/air flames in ψ-shaped mesoscale combustors of two different diameters with the variations of excess air ratio and flow rate were experimentally investigated. The variation in nanostructure and oxidation reactivity of soot was compared based on the results of high resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Results demonstrated that with an increasing excess air ratio and flow rate, the unventilated flames with bifurcated shapes were observed in both types of combustors due to the deteriorated mixing process in large flow velocity. Different effects on characteristics of soot from two combustors with the same variation of flow rate were found. For the variation in ethylene flow rate of 60–100 ml/min at excess air ratio of 0.5, the oxidation reactivity of soot from the combustor with d  = 4 mm first decreased and then slightly increased, while it decreased all the time as for the soot from the combustor with d  = 6 mm. Moreover, the significant distinctions in soot nanostructure due to the scale effect were observed. The soot from the combustor with d  = 4 mm exhibited the partial amorphous structure aggregated by a large amount of PAHs with high reactivity. Whereas among the soot from the combustor with d  = 6 mm, a typical fullerene-like structure which represented the simultaneous existence of PAHs and graphitic parts was found. The soot graphitization degree and production increased notably with the enlargement of combustor size because the higher combustion temperature and longer residence time were simultaneously obtained, which both were beneficial to soot formation and growth rate. Significantly, the lower combustion efficiency was obtained in the combustor of d  = 6 mm than 4 mm at α  = 0.5 because of the larger soot production and more existence of unburned gas. But the higher combustion efficiency was found for the 6 mm than 4 mm at α  = 1 in the case of almost no soot generation, which was due to the longer residence time.